2022
DOI: 10.1111/jcmm.17278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the TRIP13 level in breast cancer and insights into potential molecular pathways

Abstract: TRIP13 is a member of the large superfamily of the AAA + ATPase proteins and is associated with a variety of activities. Emerging evidence has shown that TRIP13 may serve as an oncogene. However, the function of TRIP13 in breast cancer (BC) has not yet been elucidated. Here, a variety of bioinformatic tools and laboratory experiments were combined to analyse the expression patterns, prognostic value and functional network of TRIP13 in BC. Multiple databases and immunohistochemistry (IHC) indicated a higher TRI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Therefore, targeting the PI3K/Akt/mTOR pathway holds promise as a therapeutic strategy in leukemia. Recently, some evidence suggested that TRIP13 can modulate the activity of the PI3K/Akt/mTOR signaling pathway so as to participate in cancer progression, such as in lung cancer, , breast cancer, and hepatocellular carcinoma . However, the relationship between TRIP13 and PI3K/Akt/mTOR in leukemia still needs to be fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, targeting the PI3K/Akt/mTOR pathway holds promise as a therapeutic strategy in leukemia. Recently, some evidence suggested that TRIP13 can modulate the activity of the PI3K/Akt/mTOR signaling pathway so as to participate in cancer progression, such as in lung cancer, , breast cancer, and hepatocellular carcinoma . However, the relationship between TRIP13 and PI3K/Akt/mTOR in leukemia still needs to be fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, we focused on TRIP13 , a member of the large superfamily of AAA+ ATPase proteins [ 45 ]. The AAA+ ATPase family is involved in a wide range of biological processes, including protein folding and DNA recombination, replication, and repair [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13 has been studied in various cancers, including colorectal, lung, breast, multiple myeloma, and ovarian cancers [14][15][16][17] . However, the role of TRIP13 in UCEC has not been elucidated to date.…”
Section: Discussionmentioning
confidence: 99%